The incredible adventures of cinnamon girl - Keil, Melissa; Lawrence, Mike (Comic book artist) (Atlanta, Georgia : Peachtree Publishers, 2016)
Alba's life of living behind a bakery, drawing comics, and watching bad television with her friends becomes chaotic when doomsday enthusiasts flock to her idyllic Eden Valley home.
Lexile by Metametrics.
A Junior Library Guild selection.
Keywords: End of the world -- Fiction; Love -- Fiction; Cartoons and comics -- Fiction; Interpersonal relations -- Juvenile fiction; Friendship -- Juvenile fiction; End of the world -- Juvenile fiction; Comic books, strips, etc; Cloth or Hardcover; Young adult fiction; Humorous - General; Romance fiction